Stigma of Mental Illness among Psychiatric Patients and their Relatives in Baghdad Society/Iraq - A. Hammo, Siham (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To highlight on the level of stigma towards mental illness among Iraqi psychiatric patients and their relatives who visit the outpatient clinic of the Psychiatric Hospital and Baghdad Medical City Hospital in Baghdad / Al – Rusafa. To provide us with basic knowledge of stigma in the family context of Iraqi communities and to assess plans to avoid feeling stigmatized towards mental illness.Design: A descriptive analytical study starting from February to December 2016 such an assessment approach is applied to achieve the objectives of the study.Methodology: A purposive (non-probability) sample of 155 individuals, including (87) patients with mental disorders and (68) relatives. The average age is 18 - 75 years old and the ratio of men to women is 1.4. \ 1 In addition to the demographic variables, which include age, gender, and educational level. The sample collected from the outpatient clinic of the Psychiatric Hospital and the City of Medicine Hospital in Baghdad\ Al - Rusafa. By relying on the construction of a questionnaire to achieve the goal of the study, based on the questionnaire of the World Psychiatric Association (WPS) and previous studies, and reviewing the literature related to the study. Determine the validity and reliability of the questionnaire by means of a group of experts and the pilot study. Data collected through a personal interview using a questionnaire form the period of 1/4/2016 to 4/30/2016. The data analyzed by descriptive and inferential statistics.Results: Through the analysis of the results, it was found that more than half (51.5%) of the sample had practices of social criticism. and there is no relationship between sex and social criticism. It also found that the practice of social criticism varies with age and educational level. As the advanced ages are tolerable for patients with mental illnesses. The results also demonstrated a statistically significant relationship between the educational level of the sample with social stigma, fear, disruption of living, and the ability to maintain friendship with patients with mental illness.Conclusion: The study notes that there is a strong relationship between social stigma and mental illness in Iraqi society through their clear attachment to religious and social beliefs and their exposure to psychological pressures because of wars. It noted that there was no relationship between gender and social stigma, but there was a relationship with the age and educational level of the patient or his relatives.Recommendation: Establish programs to combat social stigma to reduce criticism of mentally ill patients and their families, change attitudes towards mental illness, mental health workers, and psychiatric patients and their relatives by establishing psychological educational programs that are presented to the general public through newspapers, magazines, radio and television channels. Conducting further studies with a large sample size of relatives of psychiatric patients.